(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article presents an analytical overview of leading theoretical concepts of researchers and critics of the United States of the XXth century, who played the most prominent role in the long-standing academic debate on terminology outlining, and defining of semantic substratum, as well as the most characteristic attributes of the concept of «romanticism» in North American scientific studies of the national literature of the age of «American Renaissance».